2014
DOI: 10.14525/jjce.8.1.2629
|View full text |Cite
|
Sign up to set email alerts
|

Axially Loaded Steel Columns Strengthened with CFRP

Abstract: During the recent decades, Carbon Fiber-Reinforced Polymer (CFRP) composite materials have proven valuable properties and suitability to be used in the construction of new buildings and in upgrading the existing ones. The objective of this paper is to review the previous work in this area and compare it with the current experimental results to show the design equations for CFRP strengthened steel structural elements. Research findings have shown that CFRP sheets and strips are not only effective in restoring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Among these methods, the application of CFRP sheets has been proved as one of the most effective methods. CFRP material can be a perfect alternative to conventional materials for rehabilitating, strengthening and repairing of existing RC structures as well as in new constructions as alternative to steel reinforcement Soudki, El-Salakawy et al (2007), Zaman, Gutub et al (2013), Zhong, Wang et al (2013), Kalavagunta, Naganathan et al (2014), Danraka, Mahmod et al (2017), Dushimimana, Ziada et al (2018) Due to the widespread employment of CFRP in strengthening applications, many theoretical and experimental studies have focused on studying the behaviour of externally strengthened RC beams. Most of these studies have reported that the well bonded CFRP has improved the flexural strength of the structural elements and enhanced their stiffness and durability Kachlakev and McCurry (2000), Toutanji, Zhao et al (2006), Li, Xie et al (2009), Lavorato, Bergami et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, the application of CFRP sheets has been proved as one of the most effective methods. CFRP material can be a perfect alternative to conventional materials for rehabilitating, strengthening and repairing of existing RC structures as well as in new constructions as alternative to steel reinforcement Soudki, El-Salakawy et al (2007), Zaman, Gutub et al (2013), Zhong, Wang et al (2013), Kalavagunta, Naganathan et al (2014), Danraka, Mahmod et al (2017), Dushimimana, Ziada et al (2018) Due to the widespread employment of CFRP in strengthening applications, many theoretical and experimental studies have focused on studying the behaviour of externally strengthened RC beams. Most of these studies have reported that the well bonded CFRP has improved the flexural strength of the structural elements and enhanced their stiffness and durability Kachlakev and McCurry (2000), Toutanji, Zhao et al (2006), Li, Xie et al (2009), Lavorato, Bergami et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon Fiber-Reinforced Polymer (CFRP) with great material performance has been widely applied in various aspects after its invention, and its mechanical properties have also been extensively studied (Kalavagunta et al, 2014;Barile et al, 2019;Zhang et al, 2019;Yang et al, 2019;Yuan et al, 2019;Saleem et al, 2019). As an effective alternative to traditional materials for strengthening and repairing damaged structures, CFRP-reinforced bridge structure has been extensively investigated (Lu et al, 2018;Peng et al, 2014;Hosseini et al, 2019;Shukri et al, 2018;Mashrei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This because high interfacial shear stresses and peeling stresses localize in the vicinity of the plate end. Plate end debonding can be delayed by increasing the bonded length (Schnerch et al 2007;Tavakkolizadeh and Saadatmanesh 2003;Photiou et al 2006a, b;Michael et al 2005;Gu et al 2012;Jesus et al 2012;Buyukozturk and Hearing 1999;Shaat andFam 2006, 2009;Teng et al 2012;Salama and Abd-El-Meguid 2010;Yu et al 2011;Hmidan et al 2013;Ochi et al 2011;Kalavagunta et al 2014).…”
Section: Introductionmentioning
confidence: 99%